Pathological Role of Angiotensin II in Severe COVID-19 - Miesbach, Wolfgang (TH Open, 2020)
The activated renin–angiotensin system induces a prothrombotic state resulting from the imbalance between coagulation and fibrinolysis. Angiotensin II is the central effector molecule of the activated renin–angiotensin system and is degraded by the angiotensin-converting enzyme 2 to angiotensin (1–7). The novel coronavirus infection (classified as COVID-19) is caused by the new coronavirus SARS-CoV-2 and is characterized by an exaggerated inflammatory response that can lead to severe manifestations such as acute respiratory distress syndrome, sepsis, and death in a proportion of patients, mostly elderly patients with preexisting comorbidities. SARS-CoV-2 uses the angiotensin-converting enzyme 2 receptor to enter the target cells, resulting in activation of the renin–angiotensin system. After downregulating the angiotensin-converting enzyme 2, the vasoconstrictor angiotensin II is increasingly produced and its counterregulating molecules angiotensin (1–7) reduced. Angiotensin II increases thrombin formation and impairs fibrinolysis. Elevated levels were strongly associated with viral load and lung injury in patients with severe COVID-19. Therefore, the complex clinical picture of patients with severe complications of COVID-19 is triggered by the various effects of highly expressed angiotensin II on vasculopathy, coagulopathy, and inflammation. Future treatment options should focus on blocking the thrombogenic and inflammatory properties of angiotensin II in COVID-19 patients.
Keywords: renin–angiotensin system; angiotensin; inflammation; coagulopathy; COVID-19